2018
DOI: 10.1002/ajim.22862
|View full text |Cite
|
Sign up to set email alerts
|

Self‐employed individuals performing different types of work have different occupational safety and health problems

Abstract: The self-employed are a heterogeneous group of individuals. We suggest development of specific strategies that focus on workers performing "Physical work" to improve the health and safety of self-employed workers in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Eight out of sixteen studies reported a higher prevalence among men of exposure to ergonomic and biomechanical risks including repetitive tasks, uncomfortable postures, prolonged sitting or standing at work, and working at high speed [ 16 23 ]; four studies reported that women were more exposed to these hazards [ 2 , 18 , 22 , 24 ] while four studies found no differences in these exposures between men and women [ 25 28 ]. Ten out of thirteen studies reported a higher proportion of men exposed to physically demanding work including lifting and manual material handling [ 15 , 16 , 19 , 21 , 24 , 27 , 29 32 ], and three studies reported a higher prevalence of these hazards in women [ 18 , 19 , 33 ]. A higher proportion of men were exposed to occupational noise [ 2 , 27 , 31 , 34 ], vibration [ 21 , 27 , 29 , 35 ], ultraviolet radiation from sun exposure [ 31 , 36 ], radiation exposure from radioactive substances and diagnostic medical devices [ 31 , 37 ], and work-related falls [ 38 ]; no study showed women having a higher exposure than men to these occupational hazards.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight out of sixteen studies reported a higher prevalence among men of exposure to ergonomic and biomechanical risks including repetitive tasks, uncomfortable postures, prolonged sitting or standing at work, and working at high speed [ 16 23 ]; four studies reported that women were more exposed to these hazards [ 2 , 18 , 22 , 24 ] while four studies found no differences in these exposures between men and women [ 25 28 ]. Ten out of thirteen studies reported a higher proportion of men exposed to physically demanding work including lifting and manual material handling [ 15 , 16 , 19 , 21 , 24 , 27 , 29 32 ], and three studies reported a higher prevalence of these hazards in women [ 18 , 19 , 33 ]. A higher proportion of men were exposed to occupational noise [ 2 , 27 , 31 , 34 ], vibration [ 21 , 27 , 29 , 35 ], ultraviolet radiation from sun exposure [ 31 , 36 ], radiation exposure from radioactive substances and diagnostic medical devices [ 31 , 37 ], and work-related falls [ 38 ]; no study showed women having a higher exposure than men to these occupational hazards.…”
Section: Resultsmentioning
confidence: 99%
“…Ten out of thirteen studies reported a higher proportion of men exposed to physically demanding work including lifting and manual material handling [ 15 , 16 , 19 , 21 , 24 , 27 , 29 32 ], and three studies reported a higher prevalence of these hazards in women [ 18 , 19 , 33 ]. A higher proportion of men were exposed to occupational noise [ 2 , 27 , 31 , 34 ], vibration [ 21 , 27 , 29 , 35 ], ultraviolet radiation from sun exposure [ 31 , 36 ], radiation exposure from radioactive substances and diagnostic medical devices [ 31 , 37 ], and work-related falls [ 38 ]; no study showed women having a higher exposure than men to these occupational hazards. One study reported a higher prevalence of work-related heat stress among men [ 39 ] while another study reported a higher prevalence for women exposed to uncomfortable working temperatures [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that self-employed individuals who performed office work had more education, higher incomes, and the least exposure to physical, chemical, and ergonomic workplace hazards. In contrast, manual workers were older, less educated, had lower incomes, had greater exposure to workplace hazards, and had more health problems [ 20 ]. Thus, comparing workers in different occupational classes may be important for understanding the mental well-being of the self-employed population.…”
Section: Introductionmentioning
confidence: 99%